Self-reported low-energy fractures and associated risk factors in people with diabetes: A national population-based study. (January 2019) - Furtado, Sofia; Rodrigues, Ana; Dias, Sara; Branco, Jaime C.; Canhão, Helena
Abstract: Aims: Clinical risk factors and bone mineral densitometry underestimate low-energy fracture (LEF) risk in people with diabetes. We aim to estimate the prevalence of LEF in diabetics, compare with nondiabetics; and evaluate possible predictors of LEF in people with diabetes. Methods: Cross-sectional, population-based study in Portuguese subjects over 40 years-old. Estimates computed as weighted proportions/means, considering sample design. Multivariate logistic regression models to evaluate the association of diabetes and LEF; and predictors of LEF in diabetics. Results: 7675 subjects were analysed, of which 1173 reported diabetes. Diabetics were older (mean age 66.0 ± 11.49y), more frequently reported osteoporosis and falls in the previous 12 months (32.4% vs. 22.9%). Prevalence of self-reported LEF was 16.2% (95% CI:13.68–19.13) among diabetics (vs. 13.3%, 95% CI:12.14–14.57, in nondiabetics); OR for the association diabetes and LEF:1.26, 95% CI:1.01–1.58, p = 0.045 (in women, adjusted OR:1.41, 95% CI:1.05–1.89, p = 0.02). Thirty percent of diabetics reported at least one major LEF and 70% in other sites. In diabetics, LEF was independently associated with self-reported osteoporosis and falls in the previous 12 months. Conclusion: People with diabetes reported more falls and had higher prevalence of self-reported LEF. Self-reported osteoporosis and falls were associated with LEF in diabetics. Our findings emphasize the need for fracture and falls preventive measures in diabetics.